Cálculos DFT e propriedades estruturais e vibracionais sob condições extremas dos dipeptídeos L-alanil-glicina e glicil-dl-ácido aspártico - Lima, Raphaela de Araújo (2024)
In this work, the dipeptides glycyl-DL-aspartic acid monohydrate (C6H12N2O6), glycyl-DLaspartic acid (C6H10N2O5), and L-alanyl-glycine (C5H10N2O3) were studied using Raman and infrared spectroscopy techniques, combined with computational models based on Density Functional Theory (DFT), aiming to investigate the structural and vibrational properties of these materials. First-principles calculations using Density Functional Theory were performed on an isolated molecule in its zwitterionic form and with the use of the Continuum Polarization Model to simulate solvent effects. The structures of glycyl- DL-aspartic acid monohydrate and glycyl-DL-aspartic acid were initially determined by single-crystal diffraction, while the structure of L-alanyl-glycine was obtained from a crystallographic file, optimized to the lowest energy conformation, and then subjected to frequency calculations to obtain the normal vibration modes. The Gaussian09 package was used in conjunction with the B3LYP functional and the 6-311 G (d,p)++ basis set. The assignments for each normal vibration mode were made with the aid of molecular visualization software and the VEDA4 program (which provides the potential energy distribution for each mode). Raman and infrared spectroscopy experiments were performed under ambient conditions, in the range of 150 to 3500 cm−1 and 130 to 4000 cm−1, respectively. For the dipeptide glycyl-DL-aspartic acid monohydrate, thermal analysis experiments (DSC) were carried out from room temperature up to 623 K (∼ 350 ◦C), X-ray diffraction experiments with temperature variation up to 423 K (∼ 150 ◦C), Raman spectroscopy experiments with pressure variation up to 6.6 GPa, and Raman spectroscopy experiments with temperature variation, at low temperatures of 9 K (∼ -264 ◦C) and high temperatures up to 423 K (∼ 150 ◦C). For the glycyl-DL-aspartic acid dipeptide, Raman spectroscopy experiments were performed at low temperatures of 9 K (∼ -264 ◦C). For the L-alanyl-glycine dipeptide, thermal analysis experiments (DSC) were performed from room temperature up to 400 K (∼ 127 ◦C), Raman spectroscopy experiments with pressure variation up to 6.9 GPa, and Raman spectroscopy experiments with temperature variation, at low temperatures of 18 K (∼ -255 ◦C). These studies were conducted to understand the behavior of the three dipeptides under variations of these thermodynamic parameters. High-pressure experiments revealed significant changes in the Raman spectra of glycyl-DL-aspartic acid monohydrate, suggesting a phase transition around 2.0 GPa. For L-alanyl-glycine, changes were observed between 5.8 and 6.9 GPa, indicating a phase transition in the material. Regarding high-temperature measurements, significant changes were observed between 403 K and 423 K, suggesting a structural phase transition in the spectrum of glycyl-DL-aspartic acid monohydrate, likely due to the release of water molecules from the crystalline structure. At low temperatures, changes were observed in the hydrated crystal, but no significant changes were detected in its anhydrous phase. In the low-temperature Raman spectroscopy measurements of L-alanyl-glycine, changes were observed from 120 K to 18 K. Possible explanations for these structural modifications are also provided.